latex渲染测试



A

\begin{aligned}
\operatorname{Gain}(\mathrm{S}, \mathrm{A}) &=\text { Entropy }(\mathrm{S})-\sum_{i=1}^{\mathrm{n}} \frac{\left|\mathrm{S}{\mathrm{i}}\right|}{|\mathrm{S}|} \text { Entropy }\left(\mathrm{S}{\mathrm{i}}\right) \
&=\text { Entropy }(\mathrm{S})-\text { Entropy }(\mathrm{S} \mid \mathrm{A}) \
&=\mathrm{H}(\mathrm{S})-\mathrm{H}(\mathrm{S} \mid \mathrm{A})
\end{aligned}


B

$\begin{aligned} \operatorname{Gain}(\mathrm{S}, \mathrm{A}) &=\text { Entropy }(\mathrm{S})-\sum_{i=1}^{\mathrm{n}} \frac{\left|\mathrm{S}{\mathrm{i}}\right|}{|\mathrm{S}|} \text { Entropy }\left(\mathrm{S}{\mathrm{i}}\right) \ &=\text { Entropy }(\mathrm{S})-\text { Entropy }(\mathrm{S} \mid \mathrm{A}) \ &=\mathrm{H}(\mathrm{S})-\mathrm{H}(\mathrm{S} \mid \mathrm{A}) \end{aligned}$


C

$$
\begin{aligned}
\operatorname{Gain}(\mathrm{S}, \mathrm{A}) &=\text { Entropy }(\mathrm{S})-\sum_{i=1}^{\mathrm{n}} \frac{\left|\mathrm{S}{\mathrm{i}}\right|}{|\mathrm{S}|} \text { Entropy }\left(\mathrm{S}{\mathrm{i}}\right) \
&=\text { Entropy }(\mathrm{S})-\text { Entropy }(\mathrm{S} \mid \mathrm{A}) \
&=\mathrm{H}(\mathrm{S})-\mathrm{H}(\mathrm{S} \mid \mathrm{A})
\end{aligned}
$$


D

\begin{equation}
\begin{aligned}
\operatorname{Gain}(\mathrm{S}, \mathrm{A}) &=\text { Entropy }(\mathrm{S})-\sum_{i=1}^{\mathrm{n}} \frac{\left|\mathrm{S}{\mathrm{i}}\right|}{|\mathrm{S}|} \text { Entropy }\left(\mathrm{S}{\mathrm{i}}\right) \
&=\text { Entropy }(\mathrm{S})-\text { Entropy }(\mathrm{S} \mid \mathrm{A}) \
&=\mathrm{H}(\mathrm{S})-\mathrm{H}(\mathrm{S} \mid \mathrm{A})
\end{aligned}
\end{equation}